Dynamic modeling and analysis of wear in spatial hard-on-hard couple hip replacements using multibody systems methodologies - Askari, Ehsan (2015)
Wear plays a key role in primary failure of artificial hip articulations. Thus, the main goal of this work is to investigate the influence of friction-induced vibration on the predicted wear of hard hip arthroplasties. This desideratum is reached by developing a three-dimensional multibody dynamic model for a hip prosthesis taking the spatial nature of the physiological loading and motion of the human body into account. The calculation of the intra-joint contact forces developed is based on a continuous contact force approach that accounts for the geometrical and materials properties of the contacting surfaces. In addition, the friction effects due to the contact between hip components are also taken into account. The vibration of the femoral head inside the cup associated with stick-slip friction, negative-sloping friction and dynamic variation in intra-joint contact force has been also incorporated in the present hip articulation model. The friction-induced vibration increases the sliding distance of the contact point between the head and cup surfaces by altering its micro and macro trajectories, and consequently affects the wear. In the present work, the Archard’s wear law is considered and embedded in the dynamic hip multibody model, which allows for the prediction of the wear developed in the hip joint. With the purpose of having more realistic wear simulation conditions, the geometries of the acetabular cup and femoral head are updated throughout the dynamic analysis. The main results obtained from computational simulations for ceramic-on-ceramic and metal-on-metal hip prostheses are compared and validated with those available in the best-published literature. Finally, from the study performed in the present work, it can be concluded that that an important source of the high wear rates observed clinically may be due to friction-induced vibration.